Pharmacist Acceptance Decision Support System Applying AHP and COPRAS Methods - Siska Zega; Mesran Mesran (International Journal of Informatics and Data Science, 2023)
A pharmacist is a profession that is responsible for drugs both synthetic and herbal for the purpose of human health, namely starting from designing drugs, producing them, distributing them, monitoring whether the drugs prescribed by doctors are appropriate and of high quality and safe for patients. Qualified pharmacists will make it easier for companies to select pharmacists during the recruitment process. The pharmacist recruitment process requires a professional and accurate way to produce human resources that can support the quality and success of an organization. Pharmacist recruitment usually takes a long time, because the organization or company must first carefully examine and select the criteria and requirements completed by prospective pharmacists. Seeing this situation, in selecting pharmacist acceptance, a decision support system (SPK) is needed so that pharmacist acceptance can be carried out more accurately, quickly and not subjectively. Decision-making techniques using the Analytic Hierarchy Process (AHP) method developed by Thomas L Saaty are to help solve complex problems by compiling a hierarchy of criteria, subjectively assessed by interested parties and then draw various considerations to develop weights or priorities, while decision-making techniques using the COmplex PRoportional ASsessment (COPRAS) method are used to assist decision-making in making decisions on several alternative decisions to get an accurate and optimal decision. The final results obtained Billy Surkawi, S.Farm, is a pharmacist candidate who has the first highest score with a final score of 100.00, and second place Nurul andini, S.Farm with a final score of 93.66. So that the two pharmacist candidates can be proposed to become pharmacists from the results of the selection carried out.